Uji Patogenisitas Cendawan Penyebab Penyakit Daun Pada Sengon Di Persemaian Permanen Dramaga Bogor - Muhammad Alam Firmansyah; Firmansyah, Muhammad Alam; Wardhani, Diah Ayu Pramudha (Institut Pertanian Bogor, 2024)
Sengon (Paraserianthes falcataria (L.) Nielsen) is a fast-growing tree species, and its wood is readily available because it has been widely cultivated in Indonesia. Efforts to propagate sengon plants are carried out through breeding activities in the nursery. The study aimed to identify the fungus that causes leaf disease on sengon plants and calculate the extent and intensity of attacks by the fungus that causes leaf disease on sengon in the Dramaga Bogor Permanent Nursery. This research consisted of pathogenicity test activities, including field observations, Koch's postulates, and the identification of fungal species. The study used a Completely Randomized Factorial Design. The disease symptoms found around 2 months of sengon leaves at the observation site were leaf fall, leaf spot, and leaf blight. The identified fungus that caused leaf fall was Rhizoctonia sp. The fungus that caused leaf spots was Colletotrichum sp., and the fungus that caused leaf blight was Fusarium sp. Fusarium sp. resulted in the highest percentage of attacks, with a disease incidence of 67% and a disease severity of 57%. Keywords: characteristics, identification, Koch`s postulates, morphology